Immuno-Kachiks formula immunomodulates and ameliorates hepatic damage induced by monosodium glutamate in rats - Kachiko, Geoffrey; Weisheita, Anke; Ajayia, Clement Olusoji; Toloa, Casim Umba; Tusiimire, Jonans (Heliyon, 2024)
The immune system plays a vital role in controlling liver fibrosis and enhancing the pathogenesis of liver inflammation. Monosodium glutamate is a common flavor-enhancement food additive. This study evaluated the immunomodulatory and hepato-curative effects of the Immuno-Kachiks polyherbal formulation against monosodium glutamate-induced immune suppression and hepatic damage in rats. Monosodium glutamate was given orally at a 2000 mg/kg dose to male Wistar rats for three months to induce liver damage and immune suppression. After three months of successful induction, three groups were separately administered orally with Immuno-Kachiks formula at 400, 800, and 1500 mg/kg/day for 28 days. At the end of the treatment period, liver and blood samples were collected for histological and biochemical analysis. The lymphocyte count remained significantly low while the neutrophil count and the neutrophil-to-lymphocyte ratio increased significantly, despite the cessation of monosodium glutamate ingestion for 28 days. The Immuno-Kachiks formula (IKF) significantly increased the lymphocyte count, reduced the neutrophil-to-lymphocyte ratio, and normalized the neutrophil count. Neither monosodium glutamate nor the IKF significantly caused alpha-fetoprotein levels to rise or fall below normal. High doses (800 and 1500 mg/kg) of the Immuno-Kachiks formula significantly raised serum levels of aspartate aminotransferase, alkaline phosphatase, and total bilirubin. 1500 mg/kg of the IKF caused mild liver inflammation. The IKF restored the liver morphologic alterations observed in monosodium glutamate-induced liver damage in rats. The results suggest that the Immuno- Kachiks herbal formulation is a potential curative agent for early-stage liver damage and could restore suppressed adaptive immunity.
Keywords: Immuno-Kachiks formula; Immune booster; Liver disease; Suppressed immunity; Monosodium glutamate